Identifikasi Telur Parasit Helminth Berbasis Aplikasi Android untuk Pembelajaran Praktikum Daring di Era Pandemi Covid-19 - Reza Anindita; Intan Kurniawati Pramitaningrum; Arie Kusumawati (Journal of Health (JoH), 2022)
Helminth parasite is a parasite that causes worm disease in humans. There are 3 phyla of parasitic worms that cause human health problems, namely Nematodes, Trematodes, and Cestoda. One way to diagnose parasitic worms is by identifying the morphology of the eggs with digital media. Digital media helps identify worm parasitic eggs in the COVID-19 pandemic situation, namely with an Android-based worm egg identification application. This study aims to help students identify parasitic worm eggs using an application to make it easier and more practical in the COVID-19 pandemic situation. The research method is research and development using a test sample of 30 students of D-3 Medical Laboratory Technology (TLM). The data collection technique was carried out by filling out questionnaires by evaluators and TLM D-3 students. The results of the trial by the evaluator showed a percentage of 60% with the category quite suitable for use, while for students it was 71.6% with the category suitable for use. The conclusion is that further development of identification applications is needed to make it easier for students to understand, especially the key features of helminth egg identification.